Integrated metabolomics and network pharmacology to investigate the anti-hyperlipidemia effect of geniposidic acid on high-fat diet induced mice - Tang, Ruiting; Li, Kun; Liang, Mengting; Wang, Pengwei; Li, Zeyun (Frontiers in Cell and Developmental Biology, 2025)
BackgroundGeniposidic acid (GPA) has been reported to possess hypoglycemic, hypolipidemic, and choleretic properties. However, its efficacy against hyperlipidemia and the associated mechanisms remain inadequately defined.MethodsA hyperlipidemia model was established in mice using a high-fat diet, followed by a 12-week intervention with GPA or lovastatin (positive control). Serum biochemical parameters and Oil Red O staining were assessed to evaluate lipid-lowering effects. Furthermore, NMR- and MS-based metabolomics, network pharmacology, and molecular docking approaches were employed to explore the underlying mechanisms.ResultsBiochemical analysis confirmed the lipid-lowering efficacy of GPA. Urinary metabolomics revealed that both GPA and lovastatin restored disturbed metabolic profiles, notably involving the TCA cycle, glycolysis, amino acid metabolism, and ketone body synthesis. Over 40 differential metabolites were identified, constructing a comprehensive metabolic network. Network pharmacology further enriched relevant metabolic pathways and screened key targets. Molecular docking demonstrated strong binding affinities between GPA and several core proteins, including ALB, CAT, ACACA, ACHE, and SOD1, suggesting these may be potential therapeutic targets.ConclusionThis study confirmed the anti-hyperlipidemic efficacy of GPA and, through integrated metabolomics and target prediction, elucidated its potential mechanisms of action. These findings provide a scientific basis for further research and offer a promising strategy for the development of novel antihyperlipidemic agents.